Pelatihan Budidaya Kerang Abalon secara Terintegrasi dengan Budidaya Lobster dalam Rangka Implementasi Ekonomi Biru di Wilayah Pesisir Desa Ekas Buana Kabupaten Lombok Timur - Junaidi, Muhammad; Syawalina Fitria; Awan Dermawan; Mustika Raodatul Jannah (Universitas Mataram, 2025)
The Community Service Program (PKM) training program aims to improve the knowledge and skills of coastal communities in supporting the implementation of the blue economy in the Coastal Area of ​​Ekas Buana Village, East Lombok Regency. The location of the activity is Ekas Hamlet, Buana Village, Jeworaru District, East Lombok Regency. The target community that benefits from this activity is Kelombok Pasir Putih. The training method used is participatory training with a teaching and learning approach that actively involves participants. The implementation of the training consists of three stages, namely the preparation stage, implementation, monitoring and evaluation. The results of this activity are quite successful and effective in increasing the knowledge and skills of fishermen and cultivators, so it is necessary to continuously strive for activities like this in an effort to raise public awareness in supporting Ekas Bay as a blue economy development area.